Activist scholar selected works of Marilyn Gittell - Gittell, Marilyn; Gittell, Ross J. 1957-; Newman, Kathe; SAGE Knowledge (Online service). (Los Angeles, Calif. Sage, 2012)
"Activist Scholar highlights Professor Gittell's writings on community organizations, citizen participation, urban politics, the politics of education, and gender. She specialized in applied and comparative research on local, regional, national, and international policies and politics, and placed a high priority on training researchers and scholars. Marilyn Gittell was a mentor to hundreds of students in the City University of New York system, and her legacy of activism continues as her students, now on the faculties of universities across the nation, engage in important work globally."-Provided by publisher.
Part I. Educational Reform and Citizen Participation ; Prologue and Epilogue from Confrontation at Ocean Hill-Brownsville ; Education: The Decentralization-Community Control Controversy ; School Reform in New York and Chicago: Revisiting the Ecology of Local Games ; The Effect of Geography, Education and Labor Market Segregation on Women's Economic Status in New York State -- Part II: Community-Based Organizations and Community Organizing ; Chapters 1 and 2 from Limits to Citizen Participation: The Decline of Community Organizations ; Expanding Civic Opportunity: Urban Empowerment Zones ; Race and Gender in Neighborhood Development Organizations ; Community Organizing, Relationships, Collaboration, and Research: Lessons from the Fund for Community Organizing Initiative -- Part III: Women's Leadership, Social Capital, and Social Change ; Changing Women's Roles in Political Volunteerism and Reform of the City ; Activist Women: Conflicting Ideologies ; The Gender Gap: Coalescing for Power.
Includes bibliographical references.
Keywords: Gittell, Marilyn; Social participation -- Research; Political participation -- Research; Communities -- Research; Electronic books